The Influence of Price, Promotion, and Product Quality on Consumer Purchasing Decisions on Shopee E-Commerce - Budiastuti, Septiana; Syihabuddin, Muhammad (AKSIOMA : Jurnal Manajemen, 2026)
The rapid growth of e-commerce in Indonesia has triggered changes in consumer behavior when making purchasing decisions. Due to fierce competition on Shopee, aspects such as price, promotions, and product quality have become very important. The primary objective of this researcher was to evaluate the influence of these three variables on purchasing decisions, both partially and simultaneously. The methodology applied was quantitative with descriptive and associative types. The research sample consisted of 100 Shopee consumers selected using purposive sampling techniques through the distribution of online questionnaires. The data analysis process utilized multiple linear regression tests, complete with classical assumption tests, t-tests, f-tests, and determination coefficients. Based on the findings, price and product quality were proven to be significantly positively influential, with product quality being the most dominant variable. In contrast, promotion was not significantly influential when tested partially. However, when tested together, the three variables were significantly influential on purchasing decisions, with a contribution of 0.843 (Adjusted R Square).